The Role of Customer Satisfaction Mediates the Valuables of Service Quality and Location on Purchase Intention - Darwin Raja Unggul Saragih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to investigate the effect of customer satisfaction on the selective behavior of hotel guests among various choices so that it valuables the competitive advantage of hoteliers. This research was conducted using a quantitative method with a Likert scale through data collected from 120 hotel guests four stars in the capital city of Jakarta and processed using the SPSS application. Overall satisfaction is a priority in this study to achieve research objectives through service quality and location, which mediated by customers satisfaction were positively and significantly influenced purchase intention according to the results of this study. Hoteliers can use the study findings to consider competitive strategies in the HOLSERV advantage. Further research is needed so that service quality, location, and customer satisfaction can be used as tools in the marketing strategy of a hotel business.